2021
DOI: 10.3389/fonc.2021.633176
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sources of Variation to Improve the Reproducibility of Radiomics

Abstract: Radiomics is the method of choice for investigating the association between cancer imaging phenotype, cancer genotype and clinical outcome prediction in the era of precision medicine. The fast dispersal of this new methodology has benefited from the existing advances of the core technologies involved in radiomics workflow: image acquisition, tumor segmentation, feature extraction and machine learning. However, despite the rapidly increasing body of publications, there is no real clinical use of a developed rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 121 publications
(177 reference statements)
1
79
0
Order By: Relevance
“…The radiomics workflow contains a myriad of factors that can profoundly affect the resulting quantitative imaging biomarker measurement; anything from the algorithm used to reconstruct the medical image to the interpolation method utilised in an up-or down-sampling procedure can introduce variability into radiomics research (29,30). The sensitivity of extracted features to a host of procedural factors has contributed to poor scientific reproducibility in radiomics research that substantially affects its translational capacity (31). Recognising the need to ensure the scientific rigour of radiomics studies, Lambin et al (32) introduced the Radiomics Quality Score (RQS), a points-based system that rewards and penalises radiomics papers according to specific attributes of their methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…The radiomics workflow contains a myriad of factors that can profoundly affect the resulting quantitative imaging biomarker measurement; anything from the algorithm used to reconstruct the medical image to the interpolation method utilised in an up-or down-sampling procedure can introduce variability into radiomics research (29,30). The sensitivity of extracted features to a host of procedural factors has contributed to poor scientific reproducibility in radiomics research that substantially affects its translational capacity (31). Recognising the need to ensure the scientific rigour of radiomics studies, Lambin et al (32) introduced the Radiomics Quality Score (RQS), a points-based system that rewards and penalises radiomics papers according to specific attributes of their methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…These incongruous results may be due to the differing locations within the body (prostate versus liver) and/or the differing contour sizes, but only further the idea that the robustness of radiomic features should be evaluated as they can vary by location. Future radiomic studies should consider the location specific radiomic feature robustness, as the radiomic feature derived data has varying dependence on contour as seen in this study and others 3 5 , 10 12 .…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have linked several radiomic features directly to patient survival 2 . Research has shown the power of radiomics for many disease sites; however, these studies also show variability with respect to imaging modality, reconstruction algorithms, feature selection, and volume of interest (VOI) 3 9 . Several groups have studied the robustness of radiomic features with respect to contouring variability 3 5 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Image quality and the extent of image preprocessing as well as the parameters used during image preprocessing can have a substantial impact on the reliability of radiomic features and the potential of these features capturing tumor heterogeneity [22,23]. These variabilities can lead to a lack of reproducibility and generalizability of the reported radiomic features [24,25]. We also hypothesize that the variation between radiomic features can also be influenced by the tumor site.…”
Section: Introductionmentioning
confidence: 99%